The Role of the Media for Transgressing Cultural Identities during the recent Past - Galjer, Jasna (Array, 2012)
Applying methodological apparatus of cultural studies, the paper deals with key aspects and changes of the socialist and post-socialist media in creating and reconstructing social memory and cultural identity and the role of the popular culture in its "comodification". With focus on the phenomena of "false memories" the purpose is to analyse the cultural practices of the recent past through representational practices of institutional and popular culture in the period after 1991.